MRX93 syndrome (BRWD3 gene): five new patients with novel mutations. Issue 6 (29th April 2019) - Tenorio, Jair; Alarcón, Pablo; Arias, Pedro; Ramos, Feliciano J.; Campistol, Jaume; Climent, Salvador; García‐Miñaur, Sixto; Dapía, Irene; Hernández, Alicia; Nevado, Julián; Solís, Mario; Ruiz‐Pérez, Víctor L.; et al.
Abstract : Overgrowth syndromes (OGS) comprise a heterogeneous group of disorders whose main characteristic is that either the weight, height, or head circumference are above the 97th centile or 2 to 3 SD above the mean for age and sex. Additional features, such as facial dysmorphism, developmental delay or intellectual disability (ID), congenital anomalies, neurological problems and an increased risk of neoplasia are usually associated with OGS. Genetic analysis in patients with overlapping clinical features is essential, to distinguish between two or more similar conditions, and to provide appropriate genetic counseling and recommendations for follow up. In the present paper, we report five new patients (from four unrelated families) with an X‐linked mental retardation syndrome with overgrowth (XMR93 syndrome), also known as XLID‐ BRWD3 ‐related syndrome. The main features of these patients include ID, macrocephaly and dysmorphic facial features. XMR93 syndrome is a recently described disorder caused by mutations in the Bromodomain and WD‐repeat domain‐containing protein 3 ( BRWD3 ) gene. This article underscores the importance of genetic screening by exome sequencing for patients with OGS and ID with unclear clinical diagnosis, and expands the number of reported individuals with XMR93 syndrome, highlighting the clinical features of this unusual disease. Abstract : A, Clinical features of the five patients from four families with MRX93 and BRWD3 pathogenic variants. B, massive parallel sequencing and validation of the variants detected in BRWD3 .